Emotional well-being amongst female inmates in prisons: the relevance of their addictive history and their country of origin - M.M. García-Vita; F.T. Añaños-Bedriñana; M.P. Fernández-Sánchez (Sociedad Española de Sanidad Penitenciaria, 2017)
Abstract Objective: To know more about the emotional well-being of women held in prisons in Spain by analyzing the state of mental health they present and investigating the factors that affect them. Material and methods: A sample of 434 inmates in Spanish penitentiary centers was studied. An ad hoc designed questionnaire was used and a logistic regression analysis was conducted to determine the variables and to what extent they influence emotional well-being. Results: The existence of a statistically significant relationship between the well-being stages and the origin variables (region of origin of the women) and the history of substance addiction were confirmed. No significant relationship has been found for well-being levels from other variables (maternity, social or family support, gender violence or having or not having a partner). Conclusions: Having a problematic history of drug use negatively affects the levels of emotional well-being of women detained in prisons. The low levels of substance use in women of Latin American origin is related to their more positive levels of emotional well-being.